(untitled) (Quinto Sol, 2013)
In this paper, I analyse the different perspectives that are enunciated by three federal lines about political parties, during Juan Manuel de Rosas´ first government. Political, economical and institutional reasons underlie the speech of those federalist groups. Such disparity of interests and arguments assume special importance to understand the causes of the existence of such divisions inside the federal party.